Assessing gender differences in food preferences and physical activity: a population-based survey - Feraco, Alessandra; Armani, Andrea; Amoah, Isaac; Guseva, Elena; Camajani, Elisabetta; Gorini, Stefania; Strollo, Rocky; Padua, Elvira; Caprio, Massimiliano; Lombardo, Mauro (Frontiers in Nutrition, 2024)
The relationship between food tastes, meal preferences, and eating habits has been studied extensively in recent years; however, research on gender differences in these fields still needs to be addressed. The aim of this study was to investigate gender differences in food preferences and eating habits through self-administered questionnaires in a large Italian population sample. The online survey included questions on food tastes, meal preferences, eating habits, and sport involvement.The results of the study underline significant gender-specific dietary tendencies among the 2198 participants (1314 females and 884 males, average age 41.1 ± 12.7 yrs). Our analysis reveals significant gender differences in dietary preferences and eating habits. Men prefer red and processed meat, with significantly higher consumption rates than women. Women, on the other hand, show a greater inclination towards vegetables, whole grains, tofu, and high-cocoa-content dark chocolate, aligning with healthier food choices. The study also found differences in eating behaviors, including the frequency of meals, snacking habits, and hunger pa erns: women tend to eat more frequently and report higher levels of hunger in the morning, while men tend to skip snacks. Furthermore, differences extend to eating contexts, such as the speed of eating, eating out, and eating alone, with men more likely to eat quickly and dine out. Episodes of uncontrolled eating without hunger also differ, with women reporting these behaviors more frequently than men. In addition, the analysis of sports preferences showed distinct pa erns, with a lower percentage of women playing sports and those who do play sports preferring endurance and strength training, while men prefer strength training and endurance sports.These findings elucidate the complex interplay of biological, cultural, and gender-based factors in shaping dietary preferences and eating behaviors. In particular, our study reveals that gender dynamics significantly influence food choice and eating habits: women tend to choose healthier foods and eat regular meals, while men show preferences for specific tastes and meal-related behaviors. Taken together, our results highlight the importance of integrating different perspectives, thus providing valuable insights into the development of public health strategies and tailored nutrition interventions aimed at chronic disease prevention.